L'educazione medievale islandese ... - Gualdaroni, Federica (University of Salento, 2022)
It is very complex to talk about medieval Icelandic education. In fact, before the advent of Christianity, there is no evidence that allows us to create a clear and unproblematic picture of Icelandic training practices. Education initially took place within the domestic context and then continued thanks to the figure of the foster-parents: a tutor able to transmit knowledge outside the family environment. The transmission of knowledge took place mainly in oral form. Topics such as law, runes, poetry, history and genealogy were studied. Even subjects such as: magical lore, hannyroir (handicrafts/textile skills) and physical or martial skills are not left out. Between the ninth and tenth centuries, Icelandic education cannot be identified with what is commonly called school. The lack of a physical place, however, allowed to establish a relationship between teacher and pupil determined by the social rather than institutional component. Despite the few sources that have come down to us, to date, it is possible ... : È molto complesso parlare di educazione islandese medievale. Prima dell'avvento del cristianesimo, infatti non ci sono testimonianze che ci ricordano di creare un quadro chiaro e non problematico delle pratiche formative islandesi. L'aveva luogo inizialmente all'interno del contesto domestico e proseguiva poi grazie alla figura dei genitori affidatari : un istituto denotato a trasmettere l'educazione di fuori dell'ambiente familiare. La trasmissione dei saperi avveniva principalmente in forma orale. Si studiavano argomenti come: diritto, rune, poesia, storia e genealogia. Non vengono tralasciate neanche materie come: tradizioni magiche, hannyroir(artigianato/abilità tessile) e abilità fisiche o marziali. Tra il IX e il X secolo, l'istruzione islandese non può essere identificato con quello che comune viene chiamato scuola. La relazione della mancanza di un luogo fisico permetteva però di instaurare una tra insegnamento ed alunno determinato dalla componente sociale piuttosto che istituzionale. Nonostante le ...